MANAJEMEN SUMBER DAYA GURU UNTUK PENGEMBANGAN MUTU PEMBELAJARAN TAHFIDZUL QUR’AN DI SEKOLAH DASAR ISLAM TERPADU (SDIT) AHMAD YANI KOTA MALANG - Achmad Baidhowi Mukhlis (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2023)
This article discusses the management of teacher resources for the development of the quality of Tahfidzul Qur'an learning at Sekolah Dasar Islam Terpadu (SDIT) Malang City. the urgency of teacher resource management is for the effectiveness of the process of teachers entering educational institutions, recruitment, selection, development and training to how to assess the performance of the teacher so that it has an impact on the effectiveness of learning. The purpose of this study is to determine and describe 1) teacher resource planning for the development of the quality of Tahfidzul Qur'an learning at SDIT Ahmad Yani Malang, 2) the implementation of teacher resource management for the development of the quality of Tahfidzul Qur'an learning at SDIT Ahmad Yani City. Malang, 3) the results of the application of teacher resource management for the development of the quality of learning Tahfidzul Qur'an at SDIT Ahmad Yani Malang City. This type of research is qualitative using a descriptive approach. Data collection techniques carried out include observation, interviews and documentation. The results of this study are showing that teacher resource management for the development of the quality of tahfidzul qur'an learning at SDIT Ahmad Yani is going well, namely related to teacher resource planning, implementation until the results of its application in quality development, especially in the tahfidzul qur'an program.